The History of Domestication and Selection of Lucerne: A New Perspective From the Genetic Diversity for Seed Germination in Response to Temperature and Scarification - Ghaleb, Wagdi; Ahmed, Lina Qadir; Escobar-Gutiérrez, Abraham J.; Julier, Bernadette (Frontiers in Plant Science, 2021)
Lucerne (Medicago sativa), a major perennial pasture legume, belongs to a species complex that includes several subspecies with wild and cultivated populations. Stand establishment may be compromised by poor germination. Seed scarification, deterioration and temperature have an impact on germination. The objective of this study was to analyse the genetic diversity of lucerne germination in response to three factors: (1) temperature, with seven constant temperatures ranging from 5 to 40°C, was tested on 38 accessions, (2) seed scarification was tested on the same accessions at 5 and 22°C, (3) seed deterioration was tested on two accessions and two seed lots at the seven temperatures. The germination dynamics of seed lots over time was modelled and three parameters were analysed: germinability (germination capacity), maximum germination rate (maximum % of seeds germinating per time unit) and lag time before the first seed germinates. Seed scarification enhanced germinability at both temperatures and its effect was much higher on falcata and wild sativa accessions. Incomplete loss of the hardseededness trait during domestication and selection is hypothesized, indicating that the introduction of wild material in breeding programs should be followed by the selection for germinability without scarification. Seed lots with altered germinability had low germination at extreme temperatures, both cold and hot, suggesting that mild temperatures are required to promote germination of damaged seed lots. A large genetic diversity was revealed for germination (both capacity and rate) in response to temperature. All accessions had an optimal germination at 15 or 22°C and a poor germination at 40°C. The sativa varieties and landraces had a high germination from 5 to 34°C while the germination of falcata and the wild sativa accessions were weakened at 5C° or 34°C, respectively. These differences are interpreted in terms of adaptation to the climate of their geographical origin regions in order to escape frost or heat/drought risks. These new findings give insights on adaptation and domestication of lucerne in its wide geographic area. They suggest further improvement of germination is needed, especially when introducing wild material in breeding pools to remove scarification requirements and to limit differences in response to temperature.